PENGARUH JENIS DAGING DAN TINGKAT PENAMBAHAN TEPUNG TAPIOKA YANG BERBEDA TERHADAP KUALITAS BAKSO - Kgs Ahmadi; Akhadiyah Afrila; Wahyudi Ika Adhi (Universitas Tribhuwana Tunggadewi, 2007)
Bakso is traditional food made from meat dan starch. Many kinds of meat can be used as main material of bakso. This research was aimed to study the effects of different kind of meats and levels of starch proportion on bakso quality. A randomized comple design with two factors, i.e. kinds of meat and levels of strach poportions was emplyed to carry out the experiment. Two treatment factors, i.e. kinds of meat (A): A1 (beef), A2 (chicken meat), and A3 (rabbit meat); and levels of starch: P1 (20%), P2 (40%), were arranged in a completely randomized design with three replicates. Results of the study showed that kind of meat and starch proportion significantly affected bakso quality. The best bakso quality, in terms of moisture, texture, and protein was obtained from chicken meat mixed with 20% starch treatment